The Prisoners' Rights Protection in Indonesia Law System of Justice - Haidan Haidan; Edi Santoso (UIN Sunan Gunung Djati Bandung, 2016)
The aim of the paper is to examine the provision of the prisoner’s rights protection in Indonesia law system of justice and its relation to the exemption conditional (EC) in correctional institution. As an important issue, here is if the defendant override rules associated with the controversial issue in society, they will both at national and international level, such as human rights issues. The case was appeared recently, especially in the connection with the cases of exemption conditional, i.e. Pollycarpus Budihari Priyanto’s case. The case has become the center of public attention, especially after release of the Ministry of Law and Human Rights, who has been freeing the prisoners that related to the homicides Human Rights Activists (HRA) i.e Munir Said Thalib. In the community, this decision raises the pro and contra. This paper concludes that all persons deprived of their liberty will be treated with humanity and guaranteed them with respect for the inherent dignity of the human person to be in accordance with the existing rules. In this case, the government of Indonesia has given the rights of prisoners through the stages of development of the inmates according to the stage of the penal process that refers to laws and regulations and implementation of technical regulations. The paper also recommends that the need for the government to deliver data either traditionally or electronically linked plan of exemption conditional.